(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to know the role of digital human resources management in enhancing the digital culture of the University of Kufa, and spreading the culture of digitization in the context of its endeavor to support, identify and develop appropriate mechanisms that the university can adopt in carrying out its role and direction in the era of digitization of human resources, as well as determining the requirements for achieving the future visions of the university in spreading... Digital culture and identifying the difficulties that may hinder the work of universities during their performance of this future role, and how to suggest ways to confront and overcome these difficulties. Through this, the research problem can be presented with the main question: How does the university practice the digital human resources management orientation in digital culture? The researchers used the descriptive approach and surveyed the opinion of a group of directors of administrative units at the University of Kufa about the importance of human resources management at the university and for spreading digital culture in the academic community and how to implement this approach and visions. A questionnaire form was prepared and distributed to a sample of unit directors at the university, which numbered ( 33) The research reached a set of future visions in light of the digital orientation of human resources, which the university is required to do to spread the digital culture at the university, each of which includes a set of sub-future visions and implementation mechanisms, namely spreading the digital culture among students and integrating them into community service, and digital education. Technological development for administrative unit managers, increasing students’ digital awareness, and finally enhancing the values of digital citizenship among members of society.